2016
DOI: 10.1039/c5ra21356h
|View full text |Cite
|
Sign up to set email alerts
|

Novel magnetically separable ZnO/AgBr/Fe3O4/Ag3VO4 nanocomposites with tandem n–n heterojunctions as highly efficient visible-light-driven photocatalysts

Abstract: In the present work, novel magnetically separable ZnO/AgBr/Fe3O4/Ag3VO4 nanocomposites with different weight percentages of Ag3VO4 were successfully prepared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Subsequently, the electrons transfer to the conduction band of ZnO where they react with adsorbed oxygen to form the radical species (superoxide and hydroxyl radicals). Accordingly, the holes are directly involved in the degradation of the pollutants since they are not positive enough to oxidise water for the hydroxyl radicals [141,142]. The electrons and holes occupied different sites in the nanocomposite photocatalysts, which ensured efficient charge separation and the formation of the reactive species for pollutant degradation.…”
Section: Magnetite (Fe 3 O 4 )-Based Magnetic Photocatalystsmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequently, the electrons transfer to the conduction band of ZnO where they react with adsorbed oxygen to form the radical species (superoxide and hydroxyl radicals). Accordingly, the holes are directly involved in the degradation of the pollutants since they are not positive enough to oxidise water for the hydroxyl radicals [141,142]. The electrons and holes occupied different sites in the nanocomposite photocatalysts, which ensured efficient charge separation and the formation of the reactive species for pollutant degradation.…”
Section: Magnetite (Fe 3 O 4 )-Based Magnetic Photocatalystsmentioning
confidence: 99%
“…Moreover, it was shown that despite the formation of the composite photocatalysts, the presence of Fe 3 O 4 nanoparticles ensured that the photocatalysts still retained sufficient magnetic response to allow for efficient separation using an external magnetic field. Obviously, the magnetisation saturation of Fe 3 O 4 decreased sharply upon the formation of the nanocomposites due to their interaction and coverage by the non-magnetic components of the photocatalysts [141][142][143][144][145] 4 , respectively, are excited, and electrons are promoted to the conduction band, while the holes remain in the valence band. Subsequently, the electrons transfer to the conduction band of ZnO where they react with adsorbed oxygen to form the radical species (superoxide and hydroxyl radicals).…”
Section: Magnetite (Fe 3 O 4 )-Based Magnetic Photocatalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…As an n-type semiconductor (Maryam and Aziz 2016), ZnO has excellent optoelectrical behavior due to its natured wide band gap and large exciton binding energy. Nanoscale ZnO is a next-generation semiconductor material with potential applications in the catalytic and luminescent fields (Mishra et al 2015).…”
Section: Introductionmentioning
confidence: 99%